O sentido moral do conhecimento na Filosofia da educação de Roger Bacon - Lacerda, Raphaela Cândido (2019)
Roger Bacon and his project are objects of investigation that materialize in this essay. Structured in five parts, attention was drawn, at first, to drawing in brief strokes, the scenario composed of historical events marked by men and mentalities that built a path that, from the end of the Greco-Roman world, led the knowledge. over the centuries known as the Middle Ages. The objective was to answer the questions: what knowledge? What is the Middle Ages? Once the scenario was sketched, we sought to insert the figure of Roger Bacon. This was followed by Bacon's rapprochement with the influences that helped shape his thinking and his place in the debates that took place there. This path is justified by leading to the understanding of the problems that generated his concerns and the answers he sought to give his time. Inserted man in his time and known the problematization that fostered his investigations, began a dive into the nature of his work in order to understand the rationale that led him in the development of his texts, their objectives, to know the diagnosis that made of his time and the remedies that should be applied in defense of the Christian world. The origin and nature of his preambulae persuasion were presented. Emphasis was given to the paths that lead to knowledge. Authority, reason and experience appear defined, related and systematized along the Baconian corpus, which was seen in the organic character of how knowledge is understood in the relationship between philosophy and theology and in the classification of the sciences. Finally, Roger Bacon's defense was presented as a philosopher of education. One question ran through this understanding: the place of morality as a condition for knowledge that is not utilitarian in a modern conception must find its meaning in service to humanity. The methodological path followed in the exposition of this text prioritized a movement that was repeated in each chapter: exposition, description and explanation. Finally, the conclusion presented elements of a reading of the Baconian project in the light of the moral questions that require a close look at the ideal of a man who is expected to be formed and to be trained in the limits and possibilities of the sciences.